"Moderna à moda antiga" : pré-discursos e representação do feminino no discurso de autoajuda para mulheres cristãs - Vasconcelos, Mariane Rocha Camargo (2020)
In this work, from the French Discourse Analysis fundamentals, we focus on the issue of the representation of the feminine, analyzing the images of women present in self-help works aimed at Christian women. For this purpose, we use more specifically the theoretical and methodological subsidies of Paveau (2013a), who proposes a new approach to DA, endowing it with a cognitive dimension, little used in discourse studies. In this work, it is considered especially statements that present pre-discursive evidence, present in works of the genre that are currently circulating on the market. Pre-speeches are, according to this proposal, frames of beliefs, values and practices shared by a collective and that function as priorities for the production and interpretation of speeches. In short, it is about thinking frameworks that organize / categorize the world and that are transmitted via cognitive-discursive memory. The research corpus consists of 16 (sixteen) representative works of this discourse, whose analyzes reveal that it proposes to women a pattern of behavior more consistent with their emancipation, collaborating, paradoxically, for the maintenance of certain female stereotypes associated with their roles traditional. The representations of the feminine valued by this self-help evoke pre- discursive pictures that, on the one hand, place these women in domestic environments and, in addition, insist on an idea of “essence” that would “naturally” take the place of mother, wife, that is, a woman dedicated to the home and family, although, given the demands of a performance society (HAN, 2017), she is also “summoned” to take care of beauty, the body, professional success and financial etc. The analysis therefore reveals the contradiction inherent in self-help christian women discourse.